Power loss characteristics analysis of slipper pair in axial piston pump considering thermoelastohydrodynamic deformation. (3rd September 2019) - Hesheng, Tang; Yan, Ren; Jiawei, Xiang
Abstract: The power loss characteristics of slipper pair in an axial piston pump considering the thermoelastohydrodynamic deformation are investigated based on a transient power loss model. The simulation results indicate that the leakage power loss of the slipper pair increases with increasing the thermoelastohydrodynamic deformation. The viscous friction power loss decreases with an increase in the thermoelastohydrodynamic pressure. The viscous friction becomes sufficiently large under the influence of slipper surface roughness that it leads to an increase in viscous friction power loss. The pump displacement decreases with increasing the leakage rate and results in higher leakage power loss and higher friction power loss. To achieve minimum power loss in the slipper, an objective optimization study using Newton's method is applied to calculate structural parameters such as slipper inner diameter, slipper outer diameter, and orifice diameter. The proposed structural parameter optimization can be used as theoretical evidence for slipper pair design.